PERAN KOMUNIKASI DALAM PEMBANGUNAN MASYARAKAT - Akbar, Muhammad Fikri; Putubasai, Erwin; Asmaria, Asmaria (Universitas Islam Negeri Raden Intan Lampung, 2019)
The purpose of this study was to determine how to address communication in community development and determine the role of communication in community development. Development is often seen as a way to solve various problems that arise in society, especially in developing countries. Today, the role of communication is considered very important, especially in development. Communication and development are two interdependent things. The method used in this study uses the method or approach of the literature (library research). Studying literature or the library can be interpreted as a series of activities related to the method of collecting data from the library, reading, recording, and processing research documents (Zed, 2003). The result of communication about development is a strategy that emphasizes the need to socialize development with development actors in the form of spreading a message by a person or group to the public to change their attitudes, opinions, and behaviors to increase external progress and internal satisfaction in order to achieve development goals whose benefits can be perceived by all equally. From this, we can conclude that communication for development adheres to the principles of modernization of development, by positioning the government no higher than people who only form models of communication from top to bottom in society.